Following the Man of Yamhad : settlement and territory at Old Babylonian Alalah - Lauinger, Jacob. (Culture and History of the Ancient Near East, 2015)
Legal texts recording the purchase or exchange of entire settlements are among the most important cuneiform tablets discovered at Old Babylonian/Middle Bronze Age (Level VII) Alalah. Following the Man of Yamhad is the first book-length study of these legal texts and the socio-economic practice that they document. The author explores the nature of the alienated settlements, the rights enjoyed by their owners, the underlying system of land tenure, and the larger political context in which the transactions occurred. The study is supported by extensive collations and up-to-date editions of relevant legal and administrative texts. Its conclusions will be of interest to anyone working on the history, society, and economy of the Bronze Age Near East.